2002
DOI: 10.1177/000331970205300418
|View full text |Cite
|
Sign up to set email alerts
|

Mönckeberg's Sclerosis: An Unusual Presentation

Abstract: Calcification of the media of peripheral arteries is referred to as Mönckeberg's sclerosis and occurs commonly in aged individuals. However, it also occurs in younger patients with diabetes mellitus and chronic renal failure. In diabetic patients, medial calcification appears to be a strong independent predictor of cardiovascular mortality. In this report, we have presented a 20 year-old-patient with extensive peripheral artery calcification. The etiology of calcification was not identified. It has been sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Monckeberg's sclerosis has been described in case reports,3 9–12 as well as several case series 1 8 13–15. Many of these cases required limb and/or penile amputation1 12 calling into question the benign prognosis of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Monckeberg's sclerosis has been described in case reports,3 9–12 as well as several case series 1 8 13–15. Many of these cases required limb and/or penile amputation1 12 calling into question the benign prognosis of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…A calcificação da média de Monckeberg é uma condição mais prevalente em pessoas acima de 50 anos e do sexo masculino. Aparentemente, não está associada a outros fatores de risco, embora a incidência seja maior em pacientes diabéticos 1,3,4 . A prevalência na população, em estudo recente, foi de 13,3% no sexo masculino Lehto et al 7 demonstraram, em seu estudo, que a arteriosclerose de Monckeberg é um fator de risco independente para morbimortalidade por eventos cardiovasculares.…”
Section: Discussionunclassified
“…Mönckeberg's sclerosis (MS) is a degenerative and apparently non-inflammatory disease in which the media of small and medium-sized muscular arteries becomes calcified independently of atherosclerosis. Since the condition does not involve primarily the intimal layer of the artery, the lumen is kept open by the rigid media and, therefore, luminal narrowing is not a direct consequence [ 1 - 4 ]. Recent studies, however, have demonstrated that MS is a risk factor for cardiovascular disease and peripheral artery obstruction [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%